In vitro Study of Antiviral Activity of Plant Crude-extracts against the Foot and Mouth Disease Virus - Narong Chungsamarnyart; Teerapol Sirinarumitr; Wilairat Chumsing; Worawidh Wajjawalku (Agriculture and Natural Resources, 2007)
The forty-seven ethanol crude-extracts of 42 plants were studied the antiviral activity against the Foot and Mouth Disease virus (FMDV) type O, local strain KPS/005/2545. The concentration of crude-extracts were 0.2 g/ml in mixed solvents (10% Ethanol in 1% Tween 80®). Each of dissolved crude was two fold diluted with DMEM (Dulbecco’s modification of Eagle’s medium, Gibco) adding 5% fetal bovine serum for cytotoxicity testing on BHK-21 (Baby Hamster kidney cell line). The preliminary antiviral activity test, each of dissolved crude-extracts was mixed with DMEM containing FMDV at concentration 1×10 6.37 TCID50 (50% Tissue culture infective dose) for 1 hr in CO2 incubator at 37 °C. The preliminary antiviral crude-extracts were tested the antiviral activity at 20-120 second. The crude-extract of the immature fruits of Morinda elliptica L. was the highest anti-FMDV (1×103.65 TCID50) at 0.39 μg/μl concentration. The Morinda citrifolia L. crude-extract had the anti-FMDV (1×103.35 TCID50 ) at 0.19 μg/μl concentration. This indicated that the crude-extracts of the Morinda elliptica L. and the M. citrifolia L. might be the further study for practical use.